Turbo Comercio: los nuevos grandes edificios de Bogotá - Muñoz, Mauricio (Universidad Antonio Nariño, 2021)
The following article is a reflection on the continuing enlargement of scale of certain architectural interventions builtin Bogotá during the last few years, and the urban effects of such growth, more specifically, the production and appropriation of big malls as part of a modernization discourse about the city, in an absolute opposition to the policies outlined by the city’s administration, which search for a more pedestrian-driven, street-friendly metropolis, while these new buildings threaten to absorb all urban activities under one single roof, safely guarded by the commercial exchange.